Phylogenetic relationships of fruit bats(Family:Pteropodidae) in Malaysia inferred from partial mtDNA Cytochrome b gene - Jayaraj V.K; M.T. Abdullah; Andy Kho Han Guan (2006)
The taxonomic relationships of the Old World fruit bat family, Pteropodinae, by Anderson (1912) using morphological characters have been challenged by several authors. Previous studies using mitochondrial DNA (mtDNA) found major disagreement between morphology and molecular data in inferring the phylogeny of the fruit bats. Fifty-eight samples from 14 species of the Malaysian fruit bats (Family: Pteropodidae) was used in this study to examine on the phylogenogenetic relationship between species of fruit bats using 395 base pairs of partial mtDNA cytochrome b (cyt b) gene. Our phylogenetic analysis using neighbour-joining and maximum parsimony methods failed to support the monophyly of both the rousettine and cynopterine groups of the Subfamily Pteropodinae.